A normal force model for ultrasonic vibration-assisted inner-diameter slicing of hard and brittle materials. (December 2021) - Zhang, Hang; Pei, Yong-Chen; Wang, Lu-Lu; Liu, Qin-Jian
Abstract: Ultrasonic vibration-assisted inner-diameter (ID) sawing (UVAIDS) has been proved as an effective slicing process for mono-crystalline silicon in improving the surface quality of wafers. The sawing force is regarded as one of the most critical refers to evaluate the sawing performance. Modeling sawing force is significantly helpful to understand the influence of sawing variables on the sawing process. Currently, there is no publication on the sawing force model for the UVAIDS of hard and brittle materials. This investigation presents a mechanistic model for the normal force in the one-dimensional ultrasonic vibration-assisted ID sawing hard and brittle materials. Based on brittle fracture mode in material removal mechanism, the sawing force model is developed beginning from the analysis of a single diamond abrasive grain. A series of experiments on sawing mono-crystalline silicon are performed to verify this model. The experimental results show that the measured sawing forces agree with the theoretical sawing forces calculated by this model. Besides, the influence of sawing variables including ultrasonic vibration amplitude, feed rate, spindle speed, cutting-edge thickness, abrasive size, dimensions of the saw blade, and workpiece on the sawing force are also analyzed and discussed. This mechanistic model can be used to predict the normal force in the UVAIDS of hard and brittle materials. Graphical abstract: Unlabelled Image Highlights: A normal force model for ultrasonic slicing hard/brittle materials is developed. Material removal volume induced by single octahedral abrasive grain is described. The number of active diamond abrasive grains in the sawing process is analyzed. Sawing experiments for verifying this force model are designed and performed. Influence of sawing variables on the normal sawing force is discussed in detail.